Modeling Functional Connectivity for Bears Among Spawning Salmon Waterways in Haíɫzaqv (Heiltsuk) Territory, Coastal British Columbia - Ilona Mihalik; Mathieu Bourbonnais; William Housty; Kevin Starr; Paul Paquet; Chris Darimont (Ecology and Evolution, 2025)
ABSTRACT Understanding how functional connectivity can provide mobile consumers access to key resources can inform habitat management. The spatial arrangement of landscape features, for example, can affect movement among resource patches. Guided by the Haíɫzaqv (Heiltsuk) Integrated Resource Management Department (HIRMD), and within Haíɫzaqv Territory, coastal British Columbia (BC), Canada, our objectives were to (1) estimate functional connectivity for grizzly and black bears (Ursus arctos and U. americanus, respectively) among aggregations of spawning Pacific salmon (Oncorhynchus spp.), (2) identify important movement pathways for landscape planning, and (3) contribute to the growing body of functional connectivity research on dynamic ecological systems. Using circuit theory and least cost paths, we predicted movement among salmon spawning reaches within a 5618 km2 study area. Variables affecting bear movement were parameterized by drawing on the relevant literature and Haíɫzaqv Knowledge. We validated our cumulative resistance surface with observed movements as identified via genetic recapture data. Modeled current from Circuitscape suggested areas of high connectivity between salmon spawns within and among watersheds. Our least cost paths model identified principal routes, which we then ranked to illustrate possible corridors for consideration by HIRMD planners. Understanding movement among salmon spawns, a fitness‐related food, provides key information to inform landscape planning for bears. Further, our work provides an example of connectivity research codeveloped, executed, and applied with an Indigenous government.